Highlights of practical applications of survivable agents and multi-agent systems – the PAAMS collection : international workshops of PAAMS 2019, Ávila, Spain, June 26-28, 2019, proceedings /: international workshops of PAAMS 2019, Ávila, Spain, June 26-28, 2019, proceedings. (2019) - Unknown
No abstract available